Pengembangan Model Pendidikan Agama Kristen yang Berorientasi Pada Kecerdasan Intelektual dan Karakter Siswa - Rusmiani, Dewi (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
This research aims to develop a model of Christian Religious Education that is oriented towards improving students' intellectual intelligence and character building through a qualitative approach. This approach was chosen to deeply understand the learning dynamics and interactions that occur in the context of religious education.The research method used is a descriptive qualitative study with data collection techniques through participatory observation, in-depth interviews, and document analysis. The research subjects included Christian Religious Education teachers and students in a junior high school in Timika, Central Papua. Data analysis was conducted using a thematic approach to identify patterns and themes relevant to the development of learning models. The results show that the integration of teaching Christian doctrine with the development of critical and reflective thinking skills is effective in improving students' intellectual intelligence. In addition, the emphasis on Christian values such as love, integrity, and responsibility in the learning process contributes significantly to students' character building. The developed model also emphasizes the importance of local and cultural context in the delivery of material, making it more relevant and easily accepted by students. The implication of this research is the need for training for teachers in implementing a holistic learning model, which not only focuses on cognitive but also affective aspects. In addition, the involvement of the community and parents in the education process is an important supporting factor in the success of student character building.